Unraveling the Challenges of the Independence of Constitutional Court Judges Amidst the Politicization of the Judiciary in Indonesia: A Legal and Political Analysis - Hidayat, Rachmat; Herwansyah (Journal of Legal Contemplation, 2025)
The Constitutional Court (MK) as the guardian of the constitution plays an important role in upholding constitutional justice in the Indonesian constitutional system. However, the independence of MK judges is still vulnerable to political intervention, both in the legislative process and in the appointment and dismissal of judges. This study uses a normative juridical method with a legislative and conceptual approach. The results of the study show that this vulnerability is influenced by the revision of the Constitutional Court Law, which is fraught with political interests, the interference of political institutions in the selection of judges, and conflicts of interest in several controversial decisions. To strengthen the independence of the Constitutional Court, regulatory reforms based on meritocracy, external supervision through the Judicial Commission, transparency and public participation in the selection process and decisions, as well as the reinforcement of judges' ethics and integrity are needed. With these steps, it is hoped that the Constitutional Court will consistently carry out its function as the guardian of the constitution, uphold the principle of the rule of law, and protect the constitutional rights of the Indonesian people.